MENGGALI MISKONSEPSI CAHAYA DAN SIFATNYA MENGGUNAKAN TEKNIK INTERVIEW ABOUT INSTANCES (IAI) DALAM BAHASA IBU - Pita, Ela Dana; S, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to explore the misconceptions and causes of elementary students' misconceptions about light and its nature in everyday life. The Interview About Instances (IAI) technique in Sanggau Malay language was used to explore the misconceptions of 9 grade VI elementary school students. Data were analyzed qualitatively by comparing students' conceptions and conceptions of scientists and then found their causes through interviews. The results showed students had misconceptions on the concept of straight-propagating light (2 misconceptions), light could penetrate clear objects (1 misconception), reflected light (18 misconceptions), light refraction (4 misconceptions), light dispersion (7 misconceptions), and relationships between light and sight (4 misconceptions). The causes of students' misconceptions are students' errors in constructing knowledge, students are wrong in associating terms, wrong reasoning, students' answers seem to guess, students are intuitive, students fabricate answers, construction of wrong experiences, wrong preconceptions, students think humanistically. Students tend to express their conceptions based on concrete things and are limited to their own thoughts. Keywords: Misconceptions, causes of misconceptions, interviews, mother tongue.